Preclass video nanolearning or microlearning in blended medical education - Ho, Cheng-Maw; Yeh, Chi-Chuan; Wang, Jann-Yuan; Hu, Rey-Heng; Lee, Po-Huang (Frontiers in Medicine, 2025)
BackgroundShort educational videos, including microlearning (multi-concept) and nanolearning (single-concept), are increasingly used in blended medical education.ObjectiveThis study examined medical students’ preferences, learning behaviors, and outcomes when engaging with nanolearning versus amalgamated microlearning videos.MethodsA convergent parallel mixed-methods design was used. Fifth-year medical students accessed core concept videos in both formats and completed a questionnaire on format preference and learning experience. Data included questionnaire responses, online activity logs, and assessment scores, analyzed using statistical tests and thematic analysis.ResultsOf 156 students, 140 responded; 79 preferred microlearning, 18 preferred nanolearning, and 43 had no strong preference. While video engagement time did not differ, nanolearning-preferring students more often completed individual concepts. The “either” group reported higher satisfaction, and the microlearning group performed better on essay assessments. Regardless of format, students found the short videos convenient and effective.ConclusionStudents valued both nanolearning and microlearning formats for pre-class preparation. Incorporating short, flexible video formats may enhance engagement and learning in medical education.